Sistem Informasi Geografis Sebaran Tingkat Pendidikan Kota Bandung Berbasis Web - Supriadi, Irwin; s, Eki Adithya; Purwanto, Deni; M, Anisa Qolbiah (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
Education is an important aspect in developing quality human resources, where the distribution of education levels in a region is the main indicator for identifying inequality and determining the need for government intervention. Gedebage District, which is located in Bandung City, has data related to education level that still requires more structured and informative management. To support this effort, this research aims to design and implement a web-based Geographic Information System (GIS). This GIS is designed to map the distribution of education levels in an interactive, easy to access manner, and is able to provide informative and comprehensive data visualization. This system was developed using the latest technology, such as modern web frameworks and digital map integration, to ensure the accuracy and quality of the data presented. The research results show that this system can assist in analyzing education distribution, support strategic decision making, and increase information accessibility for the community and stakeholders. With its ability to present data interactively, GIS is expected to be an effective tool in supporting educational equality in Gedebage District as well as making a real contribution to educational planning in Bandung City as a whole